Description and taxonomic analysis of a tuberculated turtle leech from the Outer Banks, North Carolina, USA, provisionally identified as Placobdella multilineata Moore, 1953 (Hirudinea: Glossiphoniidae) - Sawyer, Roy T. (Zootaxa, 2021)
A tuberculated species of turtle leech is indigenous to the Great Dismal Swamp and environs of northeastern North Carolina, and differs from other known species of Placobdella. This study of hundreds of specimens for more than a decade documents its unexpected taxonomic complexity. In fact, this seemingly innocuous leech undergoes radical transformations in terms of morphology and behaviour, each adapted to a different phase of its life cycle. Biological observations reveal a progressive darkening with age which imposes taxonomic uncertainties. Furthermore, some commonly used characters are found to be unsound for taxonomic diagnosis in that they do not occur in all individuals of this species. The primary objective of this paper is a comprehensive description of this Albemarle turtle leech. The question is then asked, what distinguishes it from allied species? Toward this end, a formal taxonomic diagnosis is proposed based on details of the proboscis complex and crop-related tuberculation. This species is allied to the northern P. rugosa (Verrill, 1874) or its southern counterpart P. multilineata Moore, 1953. However, synonymy to either of these forms is problematical due to inadequacy of type descriptions. Nonetheless, in view of habitat similarity the Albemarle leech is provisionally identified as P. multilineata pending comparable studies of variability and development of other tuberculated Placobdella.